(3edNU HZjI GdhYGI aj WHbGJ GddZhjjf hGdfMGI dLdGd GdOjf GdSjhWis - (3eMeO Hf YHO Gddg Hf MejO GdMfHdi eaJi GdMfGHdIs; (3YHO GdQMef Hf CHj HcQ Hf eMeO GHf SGHb GdOjf GdNVjQj GdSjhWj, LdGd GdOjf,J (B911 (3g` s
(3ChdgG (B:s
(3hHYO agPG efJNH ef HZjI GdhYGI s
(3BNQgG (B:s
(3hEf HdZ Gddg GdCed haSM GdCLd s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
Keywords: (3GdJGQjNs